Mobile Learning as a New E-Learning Strategy - A.Baker El-Ebiary, Yousef; Abbas Al-Sammarraie, Najeeb; Salman Shukur, Ban; Almandeel, Seita; Alshamasi, Areej (International Journal of Engineering and Technology, 2018)
Mobile learning (M-learning) entails e-learning method. As a new phase of distance learning, M-learning assists the distance learning environment, decreasing the confines of the customary education. The present study discusses the presently employed devices and techniques for the accomplishment of the mobile learning target. It is concluded in this study that the use of wireless apparatus in Wi-Fi environment will consistently increase the desire to employ M-Learning technology.Â Â Â